Yield performance and quality of Indian mustard (Brassica juncea) as influenced by various nutrient management options: Yield performance and quality of Indian mustard (Brassica juncea) as influenced by various nutrient management options - A L JAT,; A G DESAI,; K P PRAJAPATI,; J R PATEL,; S K SHAH,; G P GANGWAR, (Journal of Oilseeds Research, 2020)
A field experiment was carried out during winter season of 2017-18 at Sardarkrushinagar to study the effect of different nutrient management practices on performance of Indian mustard. Results revealed that the oil content, oil yield and seed yield were significantly higher with the crop fertilized by 150% NPK with the corresponding value of increment to the tune of 5.03, 78.98 and 77.64 per cent higher over control/ no fertilizer treatment.